SPATIAL VARIATIONS IN ACCESSIBILITY TO SECONDARY SCHOOL FACILITIES IN OYO STATE (1988)
The developing countries of the world have come to realise that issues involving human resource development and basic values may need to receive attention before regional problems can be successfully attacked either directly or indirectly, through sustained national economic growth. Need arises to tackle fundamental structural problems before growth and development can proceed to a point where it positively affects remaining structural problems. In the three preceding decades, Nigerian governments (civilian and military) have made various attempts to drastically raise the income level as well as the standard and quality of life of the people at both urban and regional scales. Since independence, elaborate social welfare programmes (health and education in particular) have always been an important feature of development planning in the old Western Region (now Oyo, Ogun, Ondo, Lagos and Bendel States). Education facilities are among the public services that profoundly affect human well-being the availability of which has far reaching implications for a people's income and quality of life and increases the attractiveness of an area. More recently, Oyo State government acknowledged the need to enhance the quality of life of the people and increase their level of participation in decision-making and access to social opportunity. Between October 1, 1979 and December, 1983, Oyo State government attempted to ensure equality of access to secondary schools in social and physical term by the introduction of 'free education at all levels’ and/or proliferation of secondary schools designed to remove any barriers to the consumption of secondary school education. The policy objectives in this regard have been to improve access to educational resources by distributing them among Local government areas equitably according to need, and to correct territorial injustices and maintain efficiency in the allocation of secondary school education resources among areas. But how far have these objectives been realized? The main thrust of this study is to describe and explain the geographical variations in accessibility to secondary schools among a set of settlements and across Local government areas of the study area. The objectives therefore are to: examine the implications of State government policy (1979-1983) on accessibility of the people to secondary schools; determine the level of provision of secondary schools among Local government areas in relation to needs; examine the extent to which state citizens are better or worse off as a result of government policy on education; examine the extent to which proliferation of secondary school facilities in the State has improved distributional efficiency; and find out the major factors that determine the distribution of secondary schools in a typical region of a Third World country. In doing this work both population and secondary school data were used and they were collected from secondary sources; while data on physical distance from facility location point to user settlement) was generated from the base map. The methods of analysis employed include access opportunity model as put forward by Schneider and Symons (1971), Gini-coefficient, Lorenz curves and ratio of advantage or disadvantage, planning standards as laid down by Ministry of Education and multiple regression model. This study has revealed some facts about the distribution of secondary schools before and after 1979-1983 education programme in the State. The study shows that mass provision of secondary school facilities has increased accessibility of the population in the State to secondary school education. Enrolments in secondary schools increased from about 11% in 1978 to 36.3% in 1983. In 1978 50% of secondary schools was controlled by 39 % of the population of the State but this increased to 45% in 1983. This implies that state government policy on secondary school education has increased people's access to a larger share of the facilities by 6%. Average access opportunity to secondary schools and teachers increased by 140.51 and 108.80 percent respectively in 1983; while total population without secondary schools declined by 54 percent. Total weighted distance declined from 32,009,271 in 1978 to 9,844,663 person kilometres in 1983; while in 1983 mean weighted distance decreased by 49 percent. The mass establishment of secondary schools has also redistributed secondary school facilities in a more egalitarian direction than ever before. The spatial concentration of secondary schools and teachers in urban areas declined by 7 and 3 percent respectively while proportion of the population controlling 50 percent of secondary schools and teacher in the rural areas increased by 13 and 18 percent respectively. Thirdly, the increased number of secondary schools has not improved the distributional optimality with which the facilities were delivered. Inefficiency in the distribution of secondary school teachers and schools was overwhelming during the periods. Proliferation of secondary school facile ties has not altered the inefficiency level of social service delivery system in Nigeria. The level of inefficiency that characterizes the system has remained relatively stable over time. Fourthly, the study has shown that egalitarian approach to the provision of social services has substantially reduced inequalities and inequities in secondary school provision. The result is that disparities between the spatial pattern of need and spatial pattern of secondary school provision got reduced. There was redistribution of services in a more egalitarian direction than before. The study shows that decentralization of schools is less efficient, but it is more equitable in the sense that differences among urban and rural areas, between and within local government areas have been reduced. There was no evidence that State government made any efforts to implement the laid down distributional standards in the provision of secondary schools in the State hence the high level of inefficiency in the distribution of secondary schools among Local government areas of the State. Finally, the relationship between need (population) and provision of secondary school facilities was considerably stronger than any other identified explanatory variables implying that territorial justice exists with regards to the distribution of secondary schools in Oyo State. It shows that social and territorial justices can only be sustained if services are distributed in relation to population (need) rather than on the basis of political considerations. Areas of high population concentration attract social services and other developmental infrastructure than areas of scanty and scattered population. The observed mis-match between enrolments and provision of teachers revealed that the quantitative growth of secondary school resources was not accompanied with development. In the provision of secondary school facilities (1979-1983) there was growth but no development. The structure of this thesis is as follows. Chapter one gives the background to the study; while Chapter two deals with conceptual and theoretical framework and literature review. The extent to which mass provision of secondary schools in the State improved access opportunity to secondary schools in 1983 was examined in Chapter three; while levels of inequity in the distribution of secondary schools among Local government areas, and between urban and rural areas were examined in Chapter four. Although mass provision of secondary school, increases access opportunity of the population to secondary school education, yet it does not improve the optimal distribution of secondary school facilities among Local government areas of the State. Chapter five confirms this postulate; while Chapter six looks at factors that shape the spatial aspects of secondary school facilities in the state. Chapter seven is conclusion.